Generation of Population-Level Diversity in Anaplasma phagocytophilum msp2/p44 Gene Repertoires Through Recombination - Anthony F. Barbet; David R. Allred; Francy L. Crosby (Pathogens)
Anaplasma phagocytophilum, a tick-borne Rickettsiales, causes an emerging disease among humans and animals called granulocytic anaplasmosis. The organism expresses an immunodominant surface protein, MSP2/P44, that undergoes rapid antigenic variation during single infections due to gene conversion at a single genomic expression site with sequences from one of ~100 transcriptionally silent genes known as “functional pseudogenes”. Most studies have indicated that the predominant gene conversion mechanism is the insertion of complete central variable regions (CVRs) into the msp2/p44 expression site via homologous recombination through 5′ and 3′ conserved regions. This suggests that it is possible that persistent infections by one strain may be self-limiting due to the exhaustion of the antigenic repertoire. However, if there is substantial recombination within the functional pseudogene repertoires themselves, it is likely that these repertoires have a high rate of change. This was investigated here by analyzing the repertoires of msp2/p44 functional pseudogenes in genome-sequenced A. phagocytophilum from widely different geographic locations in the USA and Europe. The data strongly support the probability of recombination events having occurred within and between msp2/p44 repertoires that is not limited to the 5′ and 3′ conserved regions of the CVR, greatly expanding the total potential variation. Continual variation of msp2/p44 repertoires is predicted to aid the organism in overcoming existing immunity in the individual and causing superinfections among immune populations, and this may facilitate the adaptation of the microorganism to infect and cause disease in different species.